Programming multi-agent systems in AgentSpeak using Jason - Bordini, Rafael H; Bordini, Rafael H; Hübner, Jomi Fred; Wooldridge, Michael (Wiley series in agent technology, 2007)
This text provides a detailed, practical guide to building multi-agent systems using Jason, one of the most prominent agent programming languages.